32nd Joint Propulsion Conference and Exhibit 1996
DOI: 10.2514/6.1996-2780
|View full text |Cite
|
Sign up to set email alerts
|

Design of a subscale propellant slag evaluation motor using two-phase fluid dynamic analysis

Abstract: Small pressure perturbations in the Space Shuttle Reusable Solid Rocket Motor (RSRM) are caused by the periodic expulsion of molten aluminum oxide slag from a pool that collects in the aft end of the motor around the submerged nozzle nose during the last half of motor operation.It is suspected that some motors produce more slag than others due to differences in aluminum oxide agglomerate particle sizes that may relate to subtle differences in propellant ingredient characteristics such as particle size distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…For details of contour design/selection, including two-phase CFD flow simulation results and predictions, the reader is referred to an excellent treatise by Whitesides. 7 The submerged nozzle was developed for three reasons: to increase the amount of slag retained and thereby increase discrimination, to provide an empirical submerged nozzle motor test bed for analytical model calibration, and to provide a slag capture feature outwardly similar to that found in submerged nozzle motors like the RSRM. Initial testing indicated that use of the new nozzle increased slag by only 15 percent.…”
Section: Test Articlementioning
confidence: 99%
“…For details of contour design/selection, including two-phase CFD flow simulation results and predictions, the reader is referred to an excellent treatise by Whitesides. 7 The submerged nozzle was developed for three reasons: to increase the amount of slag retained and thereby increase discrimination, to provide an empirical submerged nozzle motor test bed for analytical model calibration, and to provide a slag capture feature outwardly similar to that found in submerged nozzle motors like the RSRM. Initial testing indicated that use of the new nozzle increased slag by only 15 percent.…”
Section: Test Articlementioning
confidence: 99%